2011
DOI: 10.1124/dmd.110.037507
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Hepatic but Not Renal Transporter Expression in Diet-Induced Obese Mice

Abstract: ABSTRACT:Drug pharmacokinetics can be altered in obese and diabetic subjects. In consideration of the prevalence of obesity and diabetes, characterization of transporter expression in mouse models of diabetes and obesity may be a useful tool to aid in prediction of altered drug pharmacokinetics or adverse drug reactions. It has been reported that ob/ob mice, which display a severe obesity and diabetes phenotype, exhibit multiple changes in drug transporter expression in liver and kidney. In the present study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 45 publications
(47 reference statements)
2
20
0
Order By: Relevance
“…The up-regulation of Slco10a1 could increase hepatobiliary clearance and normalise serum bile acid level. Likewise, More & Slitt (33) reported an increase in the hepatic expression levels of Abcc2 as well as Slco1a4 in a diet-induced murine model of obesity. In addition, Martin et al (13) reported an increase in the mRNA levels of Abcc2, Abcb11 and FXR in an ob/ob mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulation of Slco10a1 could increase hepatobiliary clearance and normalise serum bile acid level. Likewise, More & Slitt (33) reported an increase in the hepatic expression levels of Abcc2 as well as Slco1a4 in a diet-induced murine model of obesity. In addition, Martin et al (13) reported an increase in the mRNA levels of Abcc2, Abcb11 and FXR in an ob/ob mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Oatp1a4 and 2b1 western blots were attempted, but not successful. Details of the antibodies used are as previously published (25). …”
Section: Methodsmentioning
confidence: 99%
“…Regulation of hepatic and renal transporters has been investigated in rodent models of diabetes and obesity (Cheng et al, 2008; More and Slitt, 2011). In a study of obese mice with Type II diabetes (ob/ob strain), mRNA and protein expression of uptake transporters were decreased in the liver (Cheng et al, 2008).…”
Section: 1 Introductionmentioning
confidence: 99%